Item distribution, internal consistency, and structural validity of the German version of the DEMQOL and DEMQOL–proxy - Christian G. G. Schwab; Martin Nikolaus Dichter; Martin Berwig (BMC Geriatrics, 2018)
Abstract Background Accurate assessment of health-related quality of life as an endpoint in intervention studies is a major challenge in dementia research. The DEMQOL (29 items) and the proxy version (32 items), which is partly based on the DEMQOL, are internationally used instruments. To date, there is no information on the structural validity, item distribution, or internal consistency for the German language version of these questionnaires. Methods This psychometric study is based on a secondary data analysis of a sample of 201 outpatients with a mild form of Alzheimer’s disease (AD) and their informal caregivers. The informal caregivers who were interviewed were involved in the care of the person with AD several times per week. The analysis for the evaluation of the structural validity was performed using Mokken scale analysis. The internal consistency was calculated using the ρ of the Molenaar Sijtsma statistic and Cronbach’s α. Results For both versions, four subscales were identified: [A] “positive emotions”, [B] “negative emotions”, [C] “physical and cognitive functioning”, and [D] “daily activities and social relationships”. For both instruments, the internal consistency of all subscales was considered “good” (ρ = 0.71–0.88, α = 0.72–0.87). Conclusions The results are a first indication of good construct validity of the instruments used for the German setting. We recommend further investigations of the test-retest reliability and the inter-rater reliability of the proxy instrument.